The presence of antibiotic-resistant Staphylococcus spp. and Escherichia coli in smallholder pig farms in Uganda - Ikwap, K.; Gertzell, E.; Hansson, I.; Dahlin, L.; Selling, K.; Magnusson, Ulf; Dione, Michel M.; Jacobson, Magdalena (Springer, 2021)
Background The development of antimicrobial resistance is of global concern, and is commonly monitored by the analysis of certain bacteria. The aim of the present study was to study the antibiotic susceptibility in isolates of Staphylococcus spp. and Escherichia (E.) coli obtained from healthy pigs originating from nineteen herds enrolled in a study on herd health management in Lira district, northern Uganda. Skin and nasal swabs were analyzed for the presence of Staphylococcus spp., and selectively cultivated to investigate the presence of methicillin-resistant Staphylococcus (S.) aureus (MRSA), and rectal swabs were analyzed for the presence of E. coli. Antibiotic susceptibility was tested by broth micro-dilution. Information on the antibiotic usage and treatment regimens during the previous year was gathered using structured interviews and longitudinal data. Results In Staphylococcus spp., resistance to penicillin (10/19 isolates; 53%), fusidic acid (42%) and tetracycline (37%) were most commonly found. In E. coli, resistance to sulfamethoxazole (46/52 isolates; 88%), tetracycline (54%) and trimethoprim (17%) was most frequent. Methicillin-resistant S. aureus was found in one sample (1/50; 2%). Multi-drug resistant isolates of Staphylococcus spp. and E. coli were found in 54 and 47% of the herds, respectively. At the herd level, no associations could be made between antibiotic resistance and herd size or treatment regimens for either of the bacteria. Conclusion In conclusion, resistance to important antibiotics frequently used in animals in Uganda was common, and the presence of MRSA was demonstrated, in Ugandan pig herds.